20-43=4(x-1)-7

Simple and best practice solution for 20-43=4(x-1)-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 20-43=4(x-1)-7 equation:


Simplifying
20 + -43 = 4(x + -1) + -7

Combine like terms: 20 + -43 = -23
-23 = 4(x + -1) + -7

Reorder the terms:
-23 = 4(-1 + x) + -7
-23 = (-1 * 4 + x * 4) + -7
-23 = (-4 + 4x) + -7

Reorder the terms:
-23 = -4 + -7 + 4x

Combine like terms: -4 + -7 = -11
-23 = -11 + 4x

Solving
-23 = -11 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-23 + -4x = -11 + 4x + -4x

Combine like terms: 4x + -4x = 0
-23 + -4x = -11 + 0
-23 + -4x = -11

Add '23' to each side of the equation.
-23 + 23 + -4x = -11 + 23

Combine like terms: -23 + 23 = 0
0 + -4x = -11 + 23
-4x = -11 + 23

Combine like terms: -11 + 23 = 12
-4x = 12

Divide each side by '-4'.
x = -3

Simplifying
x = -3

See similar equations:

| 0.6(6e+9f-21g)-7f= | | (-3)/(-4) | | z=13+2(x+y)forx | | 12c=156 | | 11-19c=-18c-19+c | | -14-3m=-m+10 | | -10=-9q+7 | | 10+5f=9f-10 | | 6z-1=3+4z+6 | | (9n+4)+(9n+4)=180 | | 7n+2=-2+8n | | -u=-2u-7 | | 180(n-2)=5400 | | 5w-3=4w | | -9k+5=-10k-4 | | -9k+5=-10j-4 | | -2s-6=-s | | -34=8x-5(1-7x) | | 4j=5j-7 | | 4x+8=12x-12 | | 3g=-7+4g | | 9(t-5)+6t=5(3t+4)-10 | | m=-0.4n+28 | | y+y-y-y+y-1=18 | | -93-4v=-10v+3 | | 2x^4-9x^2-16x=0 | | 3h+3h-6h+2j-2=12 | | 2x^4-9x^2-16=0 | | 18j+2j-10j-5j-4j=16 | | 18j+2j-10-5j-4j=16 | | 13p-6p-5p=18 | | 9t+(3f)t+13= |

Equations solver categories